Walk the line: Conflict, state capacity and the political dynamics of reform - Sanjay Jain; Sumon Majumdar; Sharun Mukand (Queen's University, Department of Economics, 2011)
This paper develops a dynamic framework to analyze the political sustainability of economic reforms in developing countries. First, we demonstrate that economic reforms that are proceeding successfully may run into a political impasse, with the reform's initial success having a negative impact on its political sustainability. Second, we demonstrate that greater state capacity to make compensatory transfers to those adversely affected by reform, need not always help the political sustainability of reform, but can also hinder it. Finally, we argue that in ethnically divided societies, economic reform may be completed not despite ethnic conflict, but because of it.
Keywords: D72; O20; P16; 330; Economic Reform; State Capacity; Politics; Redistribution; Compensation; Ethnic Conflict